Isolation and culture of putative mesenchymal stem cells from equine umbilical cord Wharton’s jelly - RATHORE, N S; KASHYAP, S K; DEORA, ANUPAMA; KUMAR, PANKAJ; SINGH, J; TRIPATHI, B N; TALLURI, T R (The Indian Journal of Animal Sciences, 2018)
Despite major progress and knowledge related to the application of adult stem cells, finding alternative sources for bone marrow MSCs has remained a challenge in both humans and animals. In the current study, two protocols namely sequential enzymatic tissue digestion and tissue explant techniques were tried for successful establishment of MSC culture. Umbilical tissues were isolated each time of foaling from five sequential foalings of Marwari mares. Total cell yield, their growth potential and cryopreservation potential were studied. Adherent cell colonies could be established using both isolation methods. Both the cell populations yielded from different protocols performed similarly in terms of population doubling and CFU number value. Additionally, the cells proliferated vigourously and displayed a similar morphology of mesenchymal stem cells. The MSCs were plastic adherent, colonogenic and their morphology was polygonal and fibroblast like. During the proliferation, the cells exhibited density dependent inhibition; analysis of microbial contamination from bacteria, mycoplasma and fungi were negative; the population doubling time of the MSCs isolated was 34.8 h and 40.2 h in enzymatic treatment and tissue explant methods respectively, and diploid chromosome number of the cells was 64, and the diploid frequency was higher than 80%. In conclusion, this study reveals that both the techniques proved to be non-invasive, efficient, simple and quick for isolation and establishment of MSC culture of extra embryonic tissues from equines.